Q-PCR Based Culture-Independent Enumeration and Detection of Enterobacter: An Emerging Environmental Human Pathogen in Riverine Systems and Potable Water - Patel, Chandra B.; Shanker, Rishi; Gupta, Vijai K.; Upadhyay, Ram S. (Frontiers in Microbiology, 2016)
The availability of safe and pristine water is a global challenge when large numbers of natural and anthropogenic water resources are being depleted with faster rate. The remaining water resources are severely contaminated with various kinds of contaminants including microorganisms. Enterobacter is one of the fecal coliform bacteria of family Enterobacteriaceae. Enterobacter was earlier used as an indicator bacterium along with other fecal Coliforms namely Escherichia coli, Citrobacter and Klebsiella, but it is now known to cause various diseases in human beings. In this study, we have collected 55 samples from potable water and riverine system and proved their presence using their conserved sequences of 16S rRNA and 23S rRNA genes with the help of SYBR green real-time PCR, which showed very high specificity for the detection of Enterobacter. The Enterobacter counts in potable water were found to 1290 ± 32.89 to 1460 ± 39.42 cfu/100ml. The Enterobacter levels in surface water were 1.76 x104 ±492, 1.33 x104 ±334, 1.15 x104 ±308, 2.56 x104 ±802, 2.89 x104 ±962, 8.16 x104 ±3443 cfu/100ml; the levels of Enterobacter contamination associated with hydrophytes were 4.80 x104 ±1804, 3.48 x104 ±856, 8.50 x104 ±2074, 8.09 x104 ±1724, 6.30 x104 ±1738, 3.68 x104 ±949 cfu/10 g and the Enterobacter counts in sediments of the river, were 2.36 x104 ±703, 1.98 x104 ±530, 9.92 x104 ±3839, 6.80 x104 ±2230, 8.76 x104 ±3066 and 2.34 x104 ±732 cfu/10g at the sampling Site #1, Site # 2, Site # 3, Site # 4, Site # 5 and Site # 6 respectively. The assay could be used for the regular monitoring of potable water and other water reservoirs to check waterborne outbreaks.